2018
DOI: 10.1002/jcu.22571
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment of the internal jugular vein for the estimation of central venous pressure in hemodialysis patients: A preliminary study

Abstract: CVPni appears as a noninvasive and reliable technique. Further studies are required to confirm these results and to assess the direct clinical impact of this new method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…One prior study found that elevated JVP on physical examination had a moderate sensitivity for the diagnosis of PH [9] but that JVP-exam underestimates invasively measured RAP. This has also been demonstrated for JVP-US in non-PH populations [5,10], with underestimation of RAP by 0.5-5 cmH 2 O. Interestingly, we found that JVP-US tended to be higher than JVP-exam.…”
supporting
confidence: 84%
“…One prior study found that elevated JVP on physical examination had a moderate sensitivity for the diagnosis of PH [9] but that JVP-exam underestimates invasively measured RAP. This has also been demonstrated for JVP-US in non-PH populations [5,10], with underestimation of RAP by 0.5-5 cmH 2 O. Interestingly, we found that JVP-US tended to be higher than JVP-exam.…”
supporting
confidence: 84%